Responses of Economic Policy Uncertainty, Financial Stress and Energy-Related Uncertainty to the Shocks in US-China Tension in US - Matyakubova, Aziza; Makhmudov, Samariddin; Ozturk, Ilhan; Kurbonov, Khayrilla; Ismailov, Farrukh; Yokubboeva, Sevara; Urozov, Azamat (International Journal of Energy Economics and Policy, 2025)
The current study examines the US-China tension shocks on economic policy uncertainty, financial stress and energy-related uncertainty for the first time in the case of the United States. To this end, monthly data is utilized spanning the period from January, 2000 to September, 2022. For the empirical estimations, time-varying parameter vector autoregression (TVP-VAR) model is applied. The findings reveal that the positive responses of economic policy uncertainty, financial stress and energy-related uncertainty to the shocks in US-China tensions are observed, validating the theoretical and economic intuition in general. However, the negative effects of US-China tension on economic policy uncertainty, financial stress and energy-related uncertainty is also obtained which is specific to US, aligned with economic intuition.